Ch. 13, § 21; Ch. 22*, §§ 14-15; Ch. 35, § 7, ST. ALBANS DAILY MESSENGER SUPPLEMENT, Aug. 7, 1897, at 1, 3-10 (St. Albans, Vermont). - (:unkn) unknown (General Publisher, 1897)
No person, except on his own premises, or by the consent of the owner or occupant of the premises, or in the performance of some duty required by law, shall discharge any gun, pistol or other firearm loaded with ball or shot, or with powder only, or squibs or fire-crackers, serpent, or other preparation whereof gun-powder or other explosive substance is an ingredient, or which consists wholly of the same, within the principal inhabited parts of the city, or within twenty-five rods of any dwelling house therein, nor shall make any bonfire in or upon any street, lane or public place within the city, except by permission of the city council
--
Keywords: DISCHARGE